The protective role of vitamin D in BNT162b2 vaccine-related acute myocarditis - Tsang, Hing Wai; Chua, Gilbert T.; Tung, Keith Tsz Suen; Wong, Rosa Sze Man; Tsao, Sabrina Siu Ling; Wong, Joshua Sung Chih; Tung, Joanna Yuet Ling; Kwok, Janette Siu Yin; Yam, Jason Cheuk Sing; Chan, Godfrey Chi Fung; To, Kelvin Kai Wang; Wong, Ian Chi Kei; et al. (Frontiers in Immunology, 2025)
IntroductionVaccine-related myocarditis is recognized as a rare but important complication, especially after mass-scale mRNA COVID-19 vaccination. Knowledge regarding how to minimize the risk is limited. As NK cells can mediate acute myocarditis after mRNA COVID-19 vaccination and vitamin D may inhibit NK cells via cytokine modulation, we hypothesize that the myocarditis side effect is related to a hypovitaminosis D – mRNA vaccine – hypercytokinemia – NK cell axis, which is amendable to clinical intervention.MethodsBiochemical, immunophenotypic and genotyping assays were performed to examine vitamin D status and immune profiles in 60 patients who had BNT162b2 vaccine-related acute myocarditis.ResultsA high incidence of hypovitaminosis D (73.3%) was observed in these individuals with vaccine-related myocarditis, particularly in those presented with chest pain or intensive care unit (ICU) admission. Moreover, vitamin D level was negatively associated with peak serum cardiac troponin T level during vaccine-related myocarditis. Genotypically, the GC (vitamin D binding protein) rs4588T allele which encoded the GC2 isoform of vitamin D binding protein was a risk allele, whereas the GC1S isoform was protective. Mechanistically, hypovitaminosis D was associated with higher levels of cytokines pivotal for natural killer (NK) cells (particularly interleukin-1β (IL-1β), IL-12, Interferon-γ (IFN-γ), and IL-8) and higher percentage of CD69+ NK cells in blood, which in turn correlated with chest pain presentation.ConclusionThese data support the hypothesis that vitamin D plays a crucial role in mitigating mRNA vaccine-related myocarditis by modulating proinflammatory cytokine milieu and subsequent unfavorable NK cell activation, laying a groundwork for preventive and treatment strategies.